MANAJEMEN PENDIDIKAN DALAM MENGEMBANGKAN JIWA KEWIRAUSAHAAN SANTRI DI PONDOK PESANTREN TAHFIDZUL QUR’AN AL-MUQORROBIN SIMAN PONOROGO - Farah Niswatul Hanifah; Mada Nur Yusip Prasetya; Muhammad Sulton Fatoni; Naela Azka; Siti Nur Aizimah Izzati (STKIP Pesisir Selatan, 2026)
Objective: This study aims to examine the implementation of educational management in fostering the entrepreneurial spirit of students at Al-Muqorrobin Islamic Boarding School. The research focuses on the management process of entrepreneurial activities as well as the supporting and inhibiting factors in their implementation. Methods: This study employed a descriptive qualitative approach. Data were collected through observation, interviews, and documentation to obtain comprehensive information regarding the implementation of entrepreneurship-based educational management. Results: The findings reveal that entrepreneurial activities are systematically managed through planning, implementation, supervision, and evaluation stages. Students actively participate in various business units such as cooperatives, laundry services, and other enterprises as a form of experiential learning. These activities not only improve entrepreneurial skills but also cultivate honesty, discipline, and responsibility based on Islamic values. The success of the program is supported by effective management, careful planning, and continuous innovation, although several challenges are still encountered in practice. Novelty: This study highlights the integration of educational management and Islamic values in entrepreneurship programs within Islamic boarding schools, which contributes positively to strengthening students’ independence and entrepreneurial character.